Impact of Intercropping on the Diazotrophic Community in the Soils of Continuous Cucumber Cropping Systems - Gao, Huan; Li, Sen; Wu, Fengzhi (Frontiers in Microbiology, 2021)
Diazotrophs are important soil components that help replenish biologically available nitrogen (N) in the soil and contribute to minimizinge the use of inorganic N fertilizers in agricultural ecosystems. However, there is little understanding of how diazotrophs respond to intercropping and soil physicochemical properties in cucumber continuous-growing systems. In this study, using the nifH gene as a marker, we have examined the impacts of seven intercropping plants on diazotrophic community diversity and composition compared to a cucumber continuous cropping system at the two cropping seasons. The results showed that intercropping increased the abundance of the nifH gene, and which was negatively correlated with available phosphorous in the fall. Diazotrophic diversity and richness were higher in the rape-cucumber system than in the monoculture. Multivariate regression tree analysis revealed that the community diversity of diazotrophs was mainly shaped by soil moisture. Skermanella was the dominant genera in all the samples, which increased significantly in the chrysanthemum-cucumber system in the fall. There was no effect of intercropping on the structure of the diazotrophic community in this case. Non-metric multidimensional scaling analysis showed that cropping season had a stronger effect than intercropping on the community structure of diazotroph. Overall, our results suggest that intercropping altered the abundance and diversity rather than the structure of the diazotrophic community, which may potentially affect the N fixation ability of continuous cropping systems.